Synthesis of a sex pheromone of the longtailed mealybug, pseudococcus longispinus - Kurhade, Suresh E.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2013)
The synthesis of a recently identified and highly active sex pheromone of the longtailed mealybug, Pseudococcus longispinus is reported. A concise synthetic route, use of the under explored Meyer-Schuster rearrangement, Claisen rearrangement, and ring-closing metathesis are the highlights of this work.
Keywords: Acylation; Metathesis; pheromones; rearrangement; Total synthesis

Tetrahydrofuran ring construction through tandem iodocyclizations: synthesis of hagen's gland lactones, a pheromone of idea leuconoe , an oxylipid, and related compounds - Nookaraju, U.; Danve, Shivam S.; Kumar, Pradeep (Synlett, 2025)
A simple and efficient common route was developed for the syntheses of tetrahydrofuran-ring-containing natural products such as Hagen's gland lactones and their epimers, a pheromone of the butterfly Idea leuconoe, an oxylipid, and some valuable synthons. Brown's allylation, cross-metathesis, iodocyclization, and a tandem aminoxylation/allylation were employed as key steps in the syntheses.
Keywords: Cross-metathesis; Hagen's gland lactone; Iodocyclization; oxylipids; pheromones; tetrahydrofurans